2018
DOI: 10.2981/wlb.00429
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of mesocarnivore populations

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The best model had the lowest Akaike information criterion corrected for small sample size (AICc), and a competing model had the ΔAICc < 2.0 (Burnham & Anderson, 2002). If the estimates of b11 ${b}_{11}$ and b22 ${b}_{22}$ are significantly less than 1.0 with the 95% confidence interval (CI) below 1.0, we concluded that the populations of coyotes and wild turkeys were subjected to density dependence (Royama, 1992; Wang et al, 2009; Xingan & Wang, 2018). We calculated the model‐average predictions of coyote and wild turkey annual relative abundances as the weighted means of the predictions of the three candidate models with Akaike weights as weights.…”
Section: Methodsmentioning
confidence: 98%
“…The best model had the lowest Akaike information criterion corrected for small sample size (AICc), and a competing model had the ΔAICc < 2.0 (Burnham & Anderson, 2002). If the estimates of b11 ${b}_{11}$ and b22 ${b}_{22}$ are significantly less than 1.0 with the 95% confidence interval (CI) below 1.0, we concluded that the populations of coyotes and wild turkeys were subjected to density dependence (Royama, 1992; Wang et al, 2009; Xingan & Wang, 2018). We calculated the model‐average predictions of coyote and wild turkey annual relative abundances as the weighted means of the predictions of the three candidate models with Akaike weights as weights.…”
Section: Methodsmentioning
confidence: 98%